THE EFFECT OF CAR, FDR, NOM, AND DPK ON MURABAHAH FINANCING IN ISLAMIC BANKS BOOK 3 FOR THE YEARS 2020-2023 WITH NPF AS A MODERATING VARIABLE - Safira, Dea; Nengsih, Titin Agustin; Nazori, M; Martaliah, Nurfitri; Aprinda, Lara (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to examine the effect of murabahah financing on BUKU 3 Sharia Commercial Banks in 2020-2023, which is influenced by the capital adequacy ratio (CAR), financing to deposit ratio (FDR), net operating margin (NOM), and third-party funds (DPK). One of the data analysis techniques used in the quantitative associative method is moderated regression analysis (MRA). The research sample consisted of four banks, namely Bank Syariah Indonesia, Bank Muamalat Indonesia, Bank Mega Syariah, and Bank BTPN Syariah Tbk. This is because the entire population of this study was Islamic Commercial Banks BUKU 3. The results of the analysis show that NPF is unable to moderate the impact of FDR on murabahah financing or the relationship between CAR and murabahah financing. Conversely, NPF was found to function as a moderating factor in the relationship between NOM and murabahah financing. Conversely, NPF did not function as a moderating variable in the DPK variable that affects murabahah financing.